2019
DOI: 10.1111/1754-9485.12982
|View full text |Cite
|
Sign up to set email alerts
|

The cost to perform uterine fibroid embolisation in the Australian public hospital system

Abstract: Introduction: Uterine fibroids have the potential to cause morbidity, and there is a substantial cost to both the healthcare system and society. There is support for minimally invasive intervention, and uterine fibroid embolisation (UFE) is an established cost-effective option for women wishing for an alternative to surgery. There is a lack of local Australian costing data to compliment use in the public hospital system, and we offer a costing analysis of running a public hospital service. Methods: We reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…MSAC concluded that UAE was safe and cost‐effective, and decided to recommend public funding of fibroid embolisation services to Australian women, but placed a condition that referrals should come from a gynaecologist for Medicare to provide the rebate . A recently published cost analysis of performing UAE in the Australian public sector showed that the cost to perform the procedure including overnight admission was only AUD$3995 …”
Section: Treatment Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…MSAC concluded that UAE was safe and cost‐effective, and decided to recommend public funding of fibroid embolisation services to Australian women, but placed a condition that referrals should come from a gynaecologist for Medicare to provide the rebate . A recently published cost analysis of performing UAE in the Australian public sector showed that the cost to perform the procedure including overnight admission was only AUD$3995 …”
Section: Treatment Guidelinesmentioning
confidence: 99%
“…Interventional radiologists will also need to take greater clinical ownership for post‐procedural care and this involves having an inpatient bedcard and continuing to post‐operatively manage their patient. These issues form a major hurdle for the provision of these services in many public hospitals …”
Section: The Australian Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…The future of IR‐led research is bright in Australia and New Zealand. Through education of medical students and junior doctors, 25 nurturing of trainee radiologists 26 and cultivation of a culture of academia, the place of IR in JMIRO and role of IRs in Australia and New Zealand will only continue to flourish.…”
mentioning
confidence: 99%
“…While the FEMME trial showed better quality of life scores for myomectomy than for UFE, this was offset by higher complications (particularly haemorrhage requiring transfusion), longer hospital stay, and more patients in the UFE group reported a pregnancy. Coupling this with the low cost to perform (Clements et al 2020b ), the data to support UFE has never been more robust, and we must now permanently put scepticism in the graveyard.…”
mentioning
confidence: 99%